Hydrothermal alkaline sulfite pretreatment in the delivery of fermentable sugars from sugarcane bagasse - Tavares, João (2018)
ABSTRACT: This work aims to demonstrate the importance of hydrothermal alkaline sulfite pretreatment of sugarcane bagasse in the delivery of fermentable sugars. The pretreatment conditions, namely sodium sulfite loads (5.0-10.0 wt%), temperatures (140-160 degrees C) and reaction times (30-60 min), were tested according to the full factorial design of experiments. The employed pretreatment was characterized by high lignin removal (43-77 wt%) and partial extraction of xylans (up to 25.0 wt%), mainly by cleavage of acetyl and arabinosyl groups. After 72 h of enzymatic hydrolysis with 10 FPU (filter paper unit) cellulase and 10 CBU (cellobiose unit) -glucosidase per g of pretreated bagasse, the conversion of the carbohydrate-enriched substrates was in the range of 51 to 80 mol% for cellulose and 45 to 71 mol% for xylans. The best hydrothermal alkaline sulfite pretreatment conditions (10.0 wt% sulfite load, 150 degrees C and 45 min) were found to be highly efficient for the delivery of fermentable sugars with a yield as high as 40.4 +/- 1.9 g for 100 g native bagasse.